Using local materials for scalable marine restoration: Xiriton as a nature-enriching, low impact building material - Mason, Victoria G.; van Leeuwe, Jente; Bouma, Tjeerd J.; Sinke, Dagmar; Varley, Daniel; Heide, Tjisse van der; Temmink, Ralph J. M.; Bucher, Frank; van Belzen, Jim (Frontiers in Marine Science, 2025)
Materials currently used to produce reef structures are often limited by high production costs, negative environmental impacts or limited flexibility in design and degradability. We tested the ability of a novel concrete alternative, Xiriton, to i) exhibit adjustable erodibility using different mixtures, ii) limit the input of foreign products into the marine environment by using locally sourced building materials (e.g. local C4 grass Spartina anglica or Miscanthus giganteus, crushed shells and sand) and iii) facilitate the establishment of marine organisms. In addition to material testing of compressive strength, porosity and pH, we combined direct measurements of erosion in a fast flow flume with field measurements of erosion over time at different heights in the intertidal frame. Furthermore, we monitored the settlement of marine organisms onto Xiriton blocks placed into the field. We showed that i) while the erodibility of Xiriton can be made comparable with more conventional building materials, its degradability can be easily adjusted by altering the proportion of binding material in the mixture, ii) the use of locally sourced building materials did not reduce the structural integrity of the material but did minimise its potential long-term impacts on the environment, and that iii) Xiriton acts as a colonisable building material by facilitating the rapid establishment of species such as seaweeds, barnacles, Pacific oysters and blue mussels, and thus may enhance biodiversity. While further research is necessary to understand the longer-term behaviour and impacts of Xiriton, its simple production process, minimal short-term impacts and adjustable erodibility reveal a strong potential for its application in marine restoration using local ingredients on a global scale.